2016
DOI: 10.3389/fmicb.2016.01056
|View full text |Cite
|
Sign up to set email alerts
|

The Small Colony Variant of Listeria monocytogenes Is More Tolerant to Antibiotics and Has Altered Survival in RAW 264.7 Murine Macrophages

Abstract: Small Colony Variant (SCV) cells of bacteria are a slow-growing phenotype that result from specific defects in the electron transport chain. They form pinpoint colonies on agar plates and have a variety of phenotypic characteristics, such as altered carbon metabolism, decreased toxin and lytic enzyme production, aminoglycoside resistance, and increased intracellular persistence. They are clinically relevant in Staphylococcus aureus and Pseudomonas aeruginosa, serving as a reservoir for recurrent or prolonged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Likewise, investigations with Bacillales SCVs showed that TO efficiently killed S. aureus , B. cereus and B. subtillis but not L. monocytogenes SCVs despite its very low MIC and TO was thus bacteriostatic against that species. L. monocytogenes SCVs are indeed quite tolerant to the bactericidal effects of many classes of antibacterial agents [ 35 ]. Therefore, amelioration of the bactericidal activity of TO against this important pathogen, as seen with its derivative FC04–100, is an important breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, investigations with Bacillales SCVs showed that TO efficiently killed S. aureus , B. cereus and B. subtillis but not L. monocytogenes SCVs despite its very low MIC and TO was thus bacteriostatic against that species. L. monocytogenes SCVs are indeed quite tolerant to the bactericidal effects of many classes of antibacterial agents [ 35 ]. Therefore, amelioration of the bactericidal activity of TO against this important pathogen, as seen with its derivative FC04–100, is an important breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…coli 10129 LB_2, suggesting that the novel SNP in hemA influences resistance to gentamicin. Previous SNPs in hemA resulting in the SCV phenotype have been identified, which resulted in amino acid changes at position valine-45-glycine [3, 13], serine-232-stop [3, 13] and glutamine-225-stop [14, 15], with the latter two resulting in an early termination of the protein. The SNP we identified in this E.…”
Section: Discussionmentioning
confidence: 99%
“…HemA is a glutamyl-tRNA reductase that catalyses the initial step of porphyrin biosynthesis leading to the production of haem, which is required for respiration. Single nucleotide polymorphisms (SNPs) identified within hemA have been found to result in a SCV in several bacterial genera, including Salmonella [3, 13] and Listeria [14, 15], as well as in E. coli [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical assays to test persistence include swarming and antibiotic-induced persistence. Reduced swarming has been correlated to persistence in several pathogens [37][38][39][40][41][42][43] . All three toxin mutant strains had reduced swarming motility even when supplemented with a higher concentration of glucose (Supplemental Figure S4A).…”
Section: Conservation and Expression Of The Predicted Host-associatedmentioning
confidence: 99%